2003
DOI: 10.1287/ijoc.15.4.347.24896
|View full text |Cite
|
Sign up to set email alerts
|

A Reactive Variable Neighborhood Search for the Vehicle-Routing Problem with Time Windows

Abstract: The purpose of this paper is to present a new deterministic metaheuristic based on a modification of Variable Neighborhood Search of Mladenovic and Hansen (1997) for solving the vehicle routing problem with time windows. Results are reported for the standard 100, 200 and 400 customer data sets by Solomon (1987) and Gehring and Homberger (1999) and two real-life problems by Russell (1995). The findings indicate that the proposed procedure outperforms other recent local searches and metaheuristics. In addition f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
141
0
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(151 citation statements)
references
References 50 publications
1
141
0
9
Order By: Relevance
“…It is also important to mention that concurrent and independent work (e.g., Berger et al 2001;Bräysy 2001a, b;2003) have confirmed the main theses of this paper: the benefits of optimizing the number of vehicles and travel time independently, the value of hybrid approach, and the potential of large neighborhood search. This new generation of algorithms has, we believe, significantly enhanced our understanding of the local search approaches to the VRPTW.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…It is also important to mention that concurrent and independent work (e.g., Berger et al 2001;Bräysy 2001a, b;2003) have confirmed the main theses of this paper: the benefits of optimizing the number of vehicles and travel time independently, the value of hybrid approach, and the potential of large neighborhood search. This new generation of algorithms has, we believe, significantly enhanced our understanding of the local search approaches to the VRPTW.…”
Section: Resultssupporting
confidence: 73%
“…Its travel times are, in general, much higher than ours, but the overall algorithm is a very interesting approach to finding high-quality solutions quickly (e.g., under two minutes). Bräysy (2003) proposes a sophisticated fourstage algorithm that extends the previous approach with variable and large neighborhood search. The algorithm focuses on producing high-quality solutions, but its results seem to be weaker than ours on the Solomon benchmarks.…”
Section: Introductionmentioning
confidence: 99%
“…Constraint (11) defines the domain of the decision variable X k i j . Most researchers consider minimizing the number of vehicles as the primary objective (Bräysy, 2003), while others study it as a multi-objective problem (Ghoseiri and Ghannadpour, 2010). In the former case, a two-phase approach is often used, to minimize the vehicle number firstly and then minimize the distance with a fixed route number in the second phase.…”
Section: Problem Description and Related Workmentioning
confidence: 99%
“…With the additional requirement that the total demand on a route cannot exceed the capacity of the corresponding vehicle we get the Capacitated Vehicle Routing Problem (CVRP) (Frutos & Tohmé, 2012;Kao et al, 2013;Sitek, 2014). In turn, CVRP with Time Windows (CVRPTW) is the CVRP with the added constraint that each customer has a time window for delivery (Bräysy, 2003). In the case of single depot, the CVRPTW requires to find m routes (one for each vehicle) such that: (i) each route starts and ends at the depot, (ii) each customer is visited by just one vehicle, (iii) the total demand on a route does not exceed the capacity of the vehicle serving it, (iv) the departure and arrival times at the depot fall inside a given time window, and (v) the total cost (distance plus the penalties for violating the time windows of the customers) are minimal.…”
Section: The Vehicle Routing Problemmentioning
confidence: 99%
“…If capacity is measured only on a single dimension, the problem of loading and distributing cargo in a fleet of vehicles would be represented by CVRPTW (Bräysy, 2003). But real world goods have several features each of which corresponds to a dimension of capacity, e.g.…”
Section: The Combined Problemmentioning
confidence: 99%